ANALISIS YURIDIS PENGGUNAAN ALAT GLOBAL POSITIONING SYSTEM (GPS) OLEH PENGEMUDI KENDARAAN MENURUT UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN - Haffid Lufthi; Dessy Artina; Zainul Akmal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Global Positioning System (GPS) is a system that functions to make it easier for adriver to obtain information about his position and can perform Route Tracking and find anaddress so that it is useful for fuel and travel time destinations. The problem regarding theGlobal Positioning System (GPS) stems from the Traffic and Road Transportation Law,which drives vehicles with full concentration as stipulated in Article 106 of the Road Trafficand Transportation Law (LLAJ). This is where this article implies that the use of the GlobalPositioning System (GPS) when driving can cause accidents, so that when viewed fromArticle 106 paragraph 1 of the Traffic Law there is a lack of clarity in the rules.The conclusions that can be obtained from the results of the research are: First, theinterpretation of the law regarding